Distribution of Natural Organic Matter (NOM) in Full-scale Drinking Water Utilities of India in Eastern Region - Challenges and Issues - Mahato, Jaydev Kumar; Gupta, S. K. (Advanced Aspects of Engineering Research Vol. 5, 2021)
The presence of natural organic matter (NOM) in the water supply system is a great concern. It deteriorates the drinking water quality and results in the formation of carcinogenic Trihalomethane (THMs) compounds. The present study investigated the distribution of NOM species (TOC, DOC, UV254, and SUVA) and its challenges in various treatment stages of full-scale drinking water utilities. The Physico-chemical characteristics of raw water good complied with the Bureau of Indian Standards (BIS). During the monitoring exercise, TOC found to be the most dominant fraction of NOM, greatly influencing the treatment efficiency. The maximum concentration of TOC (3.8 mg/l) was obtained in the raw water of VWTP. The study provides immense help to the water management authority to produce safe drinking water concerning NOM.